Bio-Functional Potential and Biochemical Properties of Propolis Collected from Different Regions of Balochistan Province of Pakistan. (5th October 2022) - Akbar, Ali; Gul, Zareen; Aziz, Saliha; Sadiq, Muhammad Bilal; Achakzai, Jahangir Khan; Saeed, Shazia; Chein, Su Hlaing; Sher, Hassan
Abstract : Propolis is a well-known resinous natural substance collected by honeybees ( Apis mellifera L.) from plants exudations. Variations in chemical composition of propolis are due to different sources from which it is collected and change in climate and geographical location. In this study, different propolis samples were collected from different regions of Balochistan and examined for its chemical composition, total phenolics and total flavonoid contents, and antioxidant potential by using DPPH radical scavenging assay and antimicrobial activity. Bioactive components analysis revealed the presence of steroids, carbohydrates, flavonoids, coumarins, cardiac glycosides, quinones, anthraquinones, terpenoids, tannins, and phlobatannins at different levels. The total phenolics contents were ranged from 2.9343 ± 1.247 to 6.0216 ± 2.873 mg GAE g -1, and flavonoid contents were found to be 0.1546 ± 0.087 to 0.6586 ± 0.329 mg QE g -1, respectively. The antioxidant ability of each extract was analyzed by their concentration having 50% inhibition (I C 50 ). The propolis sample P3 possessed lower I C 50 27.07 ± 0.73 mg mL −1 with higher % inhibition of DPPH radical, and P8 showed lower % inhibition by having I C 50 84.43 ± 2.07 mg mL −1 . The antibacterial activity of all samples was analyzed against a wide group of bacteria including Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Klebsiella pneumonia and propolis extract (P4) was highly active against Klebsiella pneumoniae with the maximum diameter of zone of inhibition 20.33 ± 1.52 mm, and propolis extract (P3) showed maximum zone of inhibition against Escherichia coli 19.06 ± 1.90, while propolis extract (P2) was found less active with minimum diameter of zone of inhibition 7.46 ± 1.50 mm . The antifungal activity of extract was considered as active against the fungal species. Propolis extract (P3) showed 82% of zone of inhibition against Aspergillus Niger, and propolis extract (P1) was highly active against Aspergillus parasiticus with 80% of zone of inhibition. By comparing the vibration frequencies in wave numbers of the sample spectrograph acquired from an FTIR spectrophotometer, the functional groups present in the extracts were identified. The presence of seven elements (Fe, Zn, Mn, Ni, Pb, Cd, and Cr) was analyzed through atomic absorption spectrophotometer. The obtained concentrations were within the permissible ranges established by the World Health Organization. The GC-MS analysis revealed the presence of 80 different compounds belonged to different classes. The obtained results confirmed the imperative potential of propolis which can be used in various biological applications.